“A past that has never been present”: The Literary Experience of Childhood and Nostalgia - Salmose, Niklas (Text Matters: A Journal of Literature, Theory and Culture, 2018)
This essay explores the modernist aesthetic involved in creating a fictive, nostalgic, childhood experience. Evoking the experience of childhood through fiction is as close to actually reliving childhood as we can get. The author argues that it is possible to actually transport the reader into not only the idealized world of childhood, but more so into an embodied experience of childhood through the use of different kinds of narrative and stylistic configurations. In a stylistic and narratological analysis of three modernist novels, Virginia Woolf’s The Waves (1931), Tarjei Vesaas’ The Ice Palace [Is-slottet] (1963) and William Faulkner’s The Sound and the Fury (1929), the author explores the different ways that literature can create (or re-create) the very experience of childhood through literary style. The strategies involved in establishing a fictive experience of childhood extend from narratological choices such as free indirect style, strict focalization through a child in the narrative (which implies limitations in perception and cognitive abilities, as well as in linguistic terms) to the use of a child-like temporality, the hyperbolic use of phenomena, and an emphasis of the sensorial aspects of perception.